2018
DOI: 10.1051/ocl/2018001
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, amino acid profile, carbohydrate and mineral content of seed meals from four safflower (Carthamus tinctoriusL.) varieties grown in north-eastern Morocco

Abstract: -The purpose of this study is to complete our work on the characterization of four safflower varieties produced in the oriental region of Morocco by determining the composition of their meals. This characterization was carried out by analyzing proteins, amino acids, fibers, carbohydrates and mineral elements. The results show that the protein content varies in a range of 17.06-27.05%, fibers 63.45-69.97%, carbohydrates 12.40-17.07% and ash 3.11-3.60% on dry weight basis. The most abundant amino acid in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
1
11
2
Order By: Relevance
“…Regarding the microelements (Na, Fe, Mn, Cu, Zn, and B), both analyzed seeds contain low levels (all below 100 mg·kg −1 ). In sunflower seeds, the values found in this study for Na, Fe, and Mn were lower (446.7, 68.61 mg·kg −1 and 29 ± 2.26 mg·kg −1 ) than those reported by Mansouri et al (2010) [ 29 ].…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…Regarding the microelements (Na, Fe, Mn, Cu, Zn, and B), both analyzed seeds contain low levels (all below 100 mg·kg −1 ). In sunflower seeds, the values found in this study for Na, Fe, and Mn were lower (446.7, 68.61 mg·kg −1 and 29 ± 2.26 mg·kg −1 ) than those reported by Mansouri et al (2010) [ 29 ].…”
Section: Resultscontrasting
confidence: 82%
“…Our results were higher than those found by Kolláthová et al (2019) [ 27 ], for Ca, but lesser for K, Mg, and P in rapeseed seeds. In sunflower seeds, the values found in this study for Ca and K were higher (73.4 ± 4.6–163.6 ± 7.8 mg kg −1 ) than those reported by Kowalska et al (2019) [ 28 ] and higher than those reported by Nadeem et al (2010) [ 29 ], for Mg (73.4 ± 4.6–163.6 ± 7.8 mg·kg −1 ).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…The obtained results of amino acid composition in the seeds of Cucumis metuliferus are comparable with that reported by Karaye et al [74] and higher than the reported values of the seeds of Citrullus colocynthis fruit by [75]. The estimation of protein requirements takes into account their quantity and quality which is mainly determined by the amino acid composition particularly the essential amino acids [76]. The most abundant essential amino acid found in the seeds was phenylalanine (5.755 g/100g) while that of the juice was leucine (7.079 g/100g).…”
Section: Amino Acids Compositions Of the Seeds And Juice Of Cucumis Msupporting
confidence: 85%
“…The amino acid composition of the food samples was determined using Automated Amino Acid Analyzer (Model 6300; Beckman Coulter Inc.) as described by Mansouri et al. (2018) and Hartcamp et al. (2000).…”
Section: Methodsmentioning
confidence: 99%